Cross-cultural validation of the quality of life in hand eczema questionnaire (QOLHEQ) - Ofenloch, Robert; Weisshaar, Elke; Diepgen, Thomas L. (The journal of investigative dermatology, 2017)
The Quality of Life in Hand Eczema Questionnaire (QOLHEQ) is the only instrument assessing disease-specific health-related quality of life in patients with hand eczema. It is available in eight language versions. In this study we assessed if the items of different language versions of the QOLHEQ yield comparable values across countries. An international multicenter study was conducted with participating centers in Finland, Germany, Japan, The Netherlands, Sweden, and Turkey. Methods of item response theory were applied to each subscale to assess differential item functioning for items among countries. Overall, 662 hand eczema patients were recruited into the study. Single items were removed or split according to the item response theory model by country to resolve differential item functioning. After this adjustment, none of the four subscales of the QOLHEQ showed significant misfit to the item response theory model (P < 0.01), and a Person Separation Index of greater than 0.7 showed good internal consistency for each subscale. By adapting the scoring of the QOLHEQ using the methods of item response theory, it was possible to obtain QOLHEQ values that are comparable across countries. Cross-cultural variations in the interpretation of single items were resolved. The QOLHEQ is now ready to be used in international studies assessing the health-related quality of life impact of hand eczema.
Gesehen am 07.05.2018